2001
DOI: 10.1379/1466-1268(2001)006<0351:kmmref>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Killifish metallothionein messenger RNA expression following temperature perturbation and cadmium exposure

Abstract: Metallothionein (MT), a cysteine-rich metal binding protein, is considered to play an essential role in the regulation of intracellular metals. Induction of MT in mammalian and nonmammalian tissues following heavy metal exposure may serve as a defense mechanism and a biomarker of environmental exposure to chemical stressors such as toxic metals. In this study, MT messenger RNA (mRNA) expression was characterized in male and female nonspawning and spawning killifish (Fundulus heteroclitus) following an 8-day ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…MTs are cysteine-rich metal-binding proteins that play an essential role in the regulation of intracellular metal concentration (Chang 1995). Moreover, it is known that the expression of its transcript, generally present at basal levels, is increased also after other physiological sub-lethal stressor (Van Cleef-Toedt et al 2001). Our experiments demonstrated that MT mRNA increases, both in liver and brain, after exposure to industrial Direct violet, green, and brown dye water as well as benzene compared to the control group.…”
Section: Discussionmentioning
confidence: 51%
“…MTs are cysteine-rich metal-binding proteins that play an essential role in the regulation of intracellular metal concentration (Chang 1995). Moreover, it is known that the expression of its transcript, generally present at basal levels, is increased also after other physiological sub-lethal stressor (Van Cleef-Toedt et al 2001). Our experiments demonstrated that MT mRNA increases, both in liver and brain, after exposure to industrial Direct violet, green, and brown dye water as well as benzene compared to the control group.…”
Section: Discussionmentioning
confidence: 51%
“…This difference between laboratory and field assays is most likely caused by two main factors: (i) the differential bioavailability of metals and (ii) increased induction of MT by oxidative stress originated by organic contaminant detoxification processes. In fact, MT mRNA up-regulation has been found to change as consequence of different types of stressors in fish liver, from thermal (van Cleef-Toedt et al 2001) to oxidative stress, with MTs being nowadays recognized scavengers for ROS (Tamai et al 1993;Andrews 2000;Laity and Andrews 2007). Oxidative radicals produced as a consequence of CYP activity on organic toxicants may have triggered MT1 up-regulation, thus explaining the higher transcription in the livers of fish exposed to sediment C 2 (most contaminated by organic contaminants) in the field for 28 days when compared to animals exposed to sediment C 1 (most metal-contaminated).…”
Section: Mt1 and Hsp90aa As Stress Proteinsmentioning
confidence: 99%
“…In this work, we develop mRNA markers for monitoring A. fasciatus exposure to different kinds of pollutants, using known DNA sequences from evolutionarily related species (mainly Cyprinodonts and Percomorphs). Genes used in this analysis included the main metal-responsive metallothionein (MT) gene (Cheung et al, 2004;Navarro et al, 2009;Schlenk et al, 1995;Tom et al, 2004;Van Cleef-Toedt et al, 2001), the egg-forming, liver-expressed vitellogenin (Vtg), a known marker for estrogens (Barucca et al, 2006;Denslow et al, 2001;Garcia-Reyero et al, 2004), the dioxin-like responsive Cytochrome P4501A (CYP1A, Chung-Davidson et al, 2004;Craft et al, 2001;Quirós et al, 2007a;Quirós et al, 2007b), the oxidative stress-related gene Superoxide dismutase (SOD, Cho et al, 2006;Gonzalez et al, 2006;Pandey et al, 2003), and the protein chaperone HSP70, which are involved in the processing of missfolded proteins due to different kinds of stress (Carnevali and Maradonna, 2003;Maradonna and Carnevali, 2007;Schroder et al, 2000;Varo et al, 2002). In addition, probes for two housekeeping genes (ß actin and the elongation translation factor EF1)…”
Section: Introductionmentioning
confidence: 99%